Características clínico-epidemiológicas de pacientes pediátricos con síndrome nefrítico atendidos en el Hospital Regional de Loreto, 2017-2021 - Díaz Yumbato, Ysrael Hamlet (2023)
The nephritic syndrome is a clinical syndrome that presents as hematuria, hypertension, oliguria and edema, up to 50% of the cases can be subclinical, although it is known that this syndrome continues to have a wide distribution, there is little information in our locality about this syndrome. For this reason, the objective of this work is to determine the clinical-epidemiological characteristics of pediatric patients with nephritic syndrome treated at the Loreto Regional Hospital, 2017-2021. For this reason, a descriptive and cross-sectional study was developed, with 48 pediatric patients as a sample. Concluding that the average age of presentation was 6.25 years, the majority correspond to the male sex (62.5%), 50% of the patients come from rural areas, 10.4% of the patients presented a history of pain in the throat before of hospitalization, 64.6% had a history of skin infections. The most frequent symptoms were edema, hematuria, arterial hypertension with a frequency of 97.9%, followed by fever (77.1%), 39.6% of the patients presented cough, 31.3% presented abdominal pain, 27.1% presented headache, 20.8% % presented diarrhea and no patient presented chills or myalgia.